Mendulang Hikmah Dari Nasehat Sejarah Yang Terkandung Dalam Al-Quran - Natasya Amanda; Bella Keyza Zalianti; Reny Septiany; Khalisha Zalfa; Adelia syafira (STIKes Ibnu Sina Ajibarang, 2024)
The Koran tells about various problems faced by humans in life. It tells about everything from when a baby grows in its mother's womb, to when someone dies. It provides examples from the past to help us learn lessons and provides advice for the future. The Qur'an is special because it does not mix with what we know from science, and even contains some scientific ideas in it. It talks about things like how people live together, how money works, and how our bodies stay healthy.